2021
DOI: 10.4269/ajtmh.20-1189
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Regression Model of Water, Sanitation, and Hygiene; Treatment Coverage; and Environmental Influences on School-Level Soil-Transmitted Helminths and Schistosome Prevalence in Kenya: Secondary Analysis of the National Deworming Program Data

Abstract: According to the Kenya National School-Based Deworming program launched in 2012 and implemented for the first 5 years (2012–2017), the prevalence of soil-transmitted helminths (STH) and schistosomiasis substantially reduced over the mentioned period among the surveyed schools. However, this reduction is heterogeneous. In this study, we aimed to determine the factors associated with the 5-year school-level infection prevalence and relative reduction (RR) in prevalence in Kenya following the implementation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…This finding is supported by previous epidemiological studies that have shown high STH (especially Ascaris lumbricoides) burden among pre-school children (75). This high worm burden in these younger children is attributable to their frequent interaction with the contaminated environment especially when they are playing with the soil, eating soil (geophagy), or practicing open defecation (75,76). Therefore, changes in the mortality rate of the infectious materials in the environment will certainly influence the level of worm burdens in the PSAC owing to their high interaction with the environment.…”
Section: Discussionsupporting
confidence: 76%
“…This finding is supported by previous epidemiological studies that have shown high STH (especially Ascaris lumbricoides) burden among pre-school children (75). This high worm burden in these younger children is attributable to their frequent interaction with the contaminated environment especially when they are playing with the soil, eating soil (geophagy), or practicing open defecation (75,76). Therefore, changes in the mortality rate of the infectious materials in the environment will certainly influence the level of worm burdens in the PSAC owing to their high interaction with the environment.…”
Section: Discussionsupporting
confidence: 76%
“…trichiura . It has been shown that infection transmission and reduction of STHs can be influenced by environmental conditions, household WASH factors and population density factors [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…More often than not access to water, sanitation and hygiene is linked to socio-economic status. Moreover, factors associated with high prevalence of STHs among SAC have been documented [ 16 , 19 , 20 ]. Currently there is limited data on the prevalence of STHs and the associated risk factors in pastoral communities.…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 27 counties surveyed, 19 counties have attained EPHP while 8 counties which include Bungoma (8.1 %), Nyamira (4.8 %), Kisii (4.5 %), Narok (2.5 %), Kakamega (2.5 %), Nandi (2.4 %), Siaya (2.3 %) and Kericho (2.0 %), have not attained the threshold and shows relatively high disease burden. Previous surveys have documented challenges in the same counties related to transmission drivers including poor sanitation and hygiene conditions, slightly low treatment coverage, suitable environmental conditions for parasite persistence and economic activities that expose individuals to parasite interactions, among other factors [ 26 ]. Improved interventions targeting attainment of EPHP in these counties should be explored as well as research studies to document reasons of persistence of STH in these areas.…”
Section: Discussionmentioning
confidence: 99%